Two new species of Anopheles (Anopheles) Hyrcanus Group (Diptera: Culicidae) from the Republic of South Korea - Rueda, Leopoldo M. (Zootaxa, 2005)
Two new mosquito species belonging to the Hyrcanus Group, Anopheles (Anopheles) belenrae Rueda and An. (Ano.) kleini Rueda, are described from the Republic of South Korea, with illustrations of the larvae, pupae, adults, and male genitalia.